Experimental Study of a Broadband Parametric Acoustic Array for Sub-Bottom Profiling in Shallow Water - Ke Qu; Binbin Zou; Jingjing Chen; Yingge Guo; Runtian Wang (Shock and Vibration)
Broadband parametric acoustic arrays appear to offer advantages for shallow water sub-bottom profiling. In this paper, the performance of a broadband parametric acoustic array system was experimentally evaluated. In tank experiments using the nonlinear parabolic wave (KZK) equation, the directivity, source level, parametric acoustic array length, and penetration depth were evaluated. Based on Berktay’s far-field solution, the system’s emission signal was designed. According to sea trials of the broadband parametric acoustic array system as designed, a clear sub-bottom profile was obtained. Moreover, buried pipelines in the seabed were effectively detected, verifying the system’s effectiveness.